"Digital Twins and Augmented Observability: An Architecture Model for Experimental Oil & Gas Separator Vessel Digitization - Santos, Raphael Almeida Guimaraes dos (2021)
Digital industrial transformation has leveraged the concept of Digital Twins (DTs) and Cyber-Physical Systems (CPSs) in the Industry 4.0 context. While CPS are multididimensional and complex systems that integrate computation, communication and control of